Kondisi Sosial dan Ekonomi Masyarakat Indonesia Akibat Kebijakan Pemerintah terhadap Pandemi Covid-19 - Amalia, Neli Muna; Saputra, Saiful Adhi (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2021)
The fast spread of Coronavirus disease 2019 (Covid-19) has prompted the Indonesian government to enact policies to combat the virus. Using a literary and empirical approach, this research is utilized to create an accurate picture and provide information connected to the socio-economic situations in Indonesia as a result of the government's implementation of policies to restrict the growth rate of covid-19. The implementation of pembatasan sosial berskala besar (PSBB) policy is thought to be effective in reducing the spread of covid-19, but it has an impact on the limited space for people to move in Indonesia. The Covid-19 has also had an impact on Indonesia's economic situation, with rising unemployment rates, declining economic growth, and rising poverty rates.